Is It Possible to Develop a “Universal” Influenza Virus Vaccine? - Davide Angeletti; Jonathan W. Yewdell (2017)
Davide Angeletti and Jonathan W. Yewdell Laboratory of Viral Diseases, National Institutes of Allergy and Infectious Diseases, National Institutes of Health, Bethesda, Maryland 20892 Correspondence: jyewdellatniaid.nih.gov